Application of Ultrasonic Intelligent Imaging in L-Selectin Regulating Embryo Implantation in Mongolian Sheep Endometrium. (16th June 2022) - Wang, Changshou; Bao, Adong; Hai, Qing; Hu, Zhengxiang; Bai, Xiaoying
Abstract : In order to explore the practical application of ultrasonic imaging in the pregnancy stage of Mongolian sheep and the role of L-selectin in the embryo implantation process of Mongolian sheep, this paper systematically observed the early embryonic development by B-mode ultrasonic imaging wave diagnostic instrument with 5 MHz rectal probe and detected the expression of sLex and L-selectin in embryonic cells (jar cells) and endometrial cells (RL95-2 cells) by immunoassay to show the role of L-selectin in embryonic adhesion. The results were as follows: the correct rate of fetal sex determination by ultrasound imaging increased with the increase of pregnancy days and reached 93% at 84 days; sLex/L-selectin on the surface of Jar/RL95-2 cells is involved in the adhesion between embryo and endometrium; and when the concentration of L-selectin was 30 μ g/ml, the implantation success rate of fertilized eggs and embryos was the highest, reaching 95%. It is proved that ultrasonic intelligent imaging exploration can summarize the imaging characteristics of the early development law of sheep fetus, which provides a basis for B-ultrasound to monitor fetal growth and predict fetal age. While discussing the molecular mechanism of implantation, it provides a new idea and means for the clinical intervention of contraception and pregnancy assistance with oligosaccharide as the target.